Significant association of the novel Rf4-targeted SNP marker with the restorer for WA-CMS in different rice backgrounds and its utilization in molecular screening - Li-kai CHEN; Xian-cheng YAN; Jun-hao DAI; Si-ping CHEN; Yong-zhu LIU; Hui WANG; Zhi-qiang CHEN; Tao GUO (Journal of Integrative Agriculture, 2017)
Abstract: In the rice cytoplasmic-genetic male sterility (CMS) system, the combination of a CMS line, maintainer line and restorer line carrying the restorer gene to restore fertility, is indispensable for the development of hybrids. However, the process of screening for the trait of fertility restoration is laborious and time-consuming. In the present study, we analyzed the nucleotide sequence of the Rf4 gene, which is the major locus controlling fertility restoration, to identify allele-specific variation. A single nucleotide polymorphism (SNP) A/C at +474 in the coding sequence (CDS) was found to be capable of strictly distinguishing groups of alleles Rf4 (A) and rf4 (C). Using KASP genotyping, this valuable SNP was converted to an allele-specific PCR marker. We evaluated and validated the marker among three-line parents with different backgrounds, and the results revealed a complete correlation between SNP alleles and the fertility restoration phenotype. Molecular screening was subsequently carried out for the presence of alleles of Rf4 and Rf3 among 328 diverse rice cultivars with worldwide distribution. The results demonstrate that this SNP marker could be the optimal choice for the molecular identification of potential restorers.